Students' Responses to the Korean Wave Phenomenon (Among Sociology Education Program Students at FKIP Tanjungpura University) - Nurhafizha, Nurhafizha; Imran, Imran (International Journal Ethnic, Racial and Cultural Heritage, 2025)
This research was conducted with the aim of analyzing female college students' responses to the Korean Wave phenomenon that has become a global trend lately. In addition, this study also aims to understand the impact of the Korean Wave on the knowledge, judgment, and actions of female college students as fans of the Korean Wave phenomenon. Korean Wave itself is a term that refers to various aspects of South Korean popular culture, such as K-pop music, K-dramas, fashion, food, and so on that are starting to go global among teenagers to young adults in various countries, one of which is Indonesia. This research uses a descriptive qualitative method. The data collection techniques used were observation, documentation and in-depth interviews conducted with a number of female students of the Sociology Education study program, FKIP, Tanjungpura University, Pontianak. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. The analysis in this study used 6 informants. The research found that Korean Wave has a significant influence on female students. College students show high interest in K-Pop music, Korean dramas, and Korean cuisine. They are also active in consuming K-Pop content and are members of a fandom community known as K-Popers. In addition, they also showed that they adopt diverse aspects of Korean culture into their daily lives. This study also found that some female college students have mixed assessments of the Korean Wave. This study can be concluded that the Korean Wave is not a phenomenon that only affects the entertainment industry, however, it also affects the cultural and social identity of female students in the Sociology Education study program, FKIP, Tanjungpura University, Pontianak.